Atmospheric dust dynamics in southern South America: A 14-year modern dust record in the loessic Pampean region - Cosentino, Nicolas Juan; Gaiero, Diego Marcelo; Torre, Gabriela; Pasquini, Andrea Ines; Coppo, Renata; Arce, Juan Mateo; Velez, Georgina (Sage Publications, 2023)
Mineral aerosols profoundly impact global climate. Modeling of the dust cycle is the main tool used to gauge this effect. However, the scarcity of in situ modern dust flux measurements is the main reason why validation of existing models is hampered. We present the first long-term (14-year) record of dust flux in the Pampas, southern South America, home to the largest loess deposit in the Southern Hemisphere. Measured 14-year mean deposition (40 g m−2 year−1) and horizontal (362 g m−2 year−1) fluxes imply that current models underestimate the power of the central Pampas as a dust sink. Based on cross-spectral analysis, both wet and, to a lesser extent, dry deposition are found to play significant roles in atmospheric dust extraction. Dust is sourced regionally from the South American Arid Diagonal and from the shores of Mar Chiquita lake (~260 km), which we find to be the main contributor of dust particles >30 µm. Cross-spectral and satellite image analyses show that surface wind speed and precipitation at the Puna-Altiplano Plateau are controlling factors for horizontal dust flux in the Pampas. El Niño Southern Oscillation probably plays a role in controlling interannual horizontal dust flux periodicities. Finally, preliminary comparisons between modern vertical dust fluxes and loess accumulation rates point to the Pampas as a more powerful dust sink during the last deglaciation and Antarctic Cold Reversal (18–12.5 ka).